Conductometric Studies of Simple Electrolytes and Micellar Solutions - GHOWSI, KIUMARS; DAGHIGHI, ARASH; GHOWSI, HOSEIN (Asian Journal of Chemistry, 2010)
A new technique was developed to measure the conductance of a conductive type of cell. A theoretical model was designed. Similar to spectroscopy in IR/UV-vis, the frequency of the input signal was swept from a few hertz to 1 MHz and the conductance of the whole cell was measured. The developed theoretical model was in good agreement with the experimental results. Change of conductance with concentration between simple electrolytes such as HCl solution with micellar solution was compared. The concentration limits of HCl as low as 45 μM was measured. Critical micellar concentrations of two types of micelles, sodium salt of dodecyl sulfate and 1-cetylpyridinium chloride monohydrate were measured. It was shown that a voltage divider circuit can be used for conductometric titrations.